Shift in Cyanobacteria Community Diversity in Hot Springs of India. Issue 2 (7th February 2018) - Subudhi, Enketeswara; Sahoo, Rajesh Kumar; Gaur, Mahendra; Singh, Archana; Das, Aradhana
ABSTRACT: Two ecologically distinct tropical sulfur-rich alkaline hot springs, Taptapani at 48°C harboring mesophiles and Atri at 58°C comprising thermophiles situated in the Eastern Ghats foothills of India, differ in their geochemical conditions, and provide an interesting platform to unravel the eco-physiological reasons behind the differential cyanobacterial diversity. The predominance of mesophilic Arthronema (83.81%) in Taptapani and shifting predominance of thermophilic Leptolyngbya (96.25%) in Atri as discovered through 16S rRNA gene Illumina sequencing of their metagenomics DNA as a function of temperature are the intriguing features of the present study. Differential presence of the cyanobacterial community at the phylum level in these two hot springs was found to be correlated with the unequal coexistence of Chloroflexi, Taptapani the non-cyanobacteria members and the possible influence of physiochemical parameters including temperature. Variation in cyanobacterial diversity and composition of these hot springs as revealed through sequence analysis were also evinced by respective differences in richness, evenness, and Shannon diversity indices.